2019
DOI: 10.1371/journal.pone.0202377
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning image recognition enables efficient genome editing in zebrafish by automated injections

Abstract: One of the most popular techniques in zebrafish research is microinjection. This is a rapid and efficient way to genetically manipulate early developing embryos, and to introduce microbes, chemical compounds, nanoparticles or tracers at larval stages. Here we demonstrate the development of a machine learning software that allows for microinjection at a trained target site in zebrafish eggs at unprecedented speed. The software is based on the open-source deep-learning library Inception v3. In a first step, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Significantly, IY microinjections did not result in a proper intrabody distribution of the compounds. This is somewhat unexpected as the IY exposure route is often used to deliver DNA and morpholino's, and infect (eleuthero-)embryos with viruses, bacterial and cancer cells, especially since the technique is easy to perform [ 17,22,[33][34][35] ]. However, in case of small chemicals, it appears that the molecules can become entrapped in the yolk that represents a dense amphiphilic environment consisting largely of cholesterol (40% of total lipid), phosphatidylcholine (17%), and phospholipo-glycoproteins (i.e., vitellogenins) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, IY microinjections did not result in a proper intrabody distribution of the compounds. This is somewhat unexpected as the IY exposure route is often used to deliver DNA and morpholino's, and infect (eleuthero-)embryos with viruses, bacterial and cancer cells, especially since the technique is easy to perform [ 17,22,[33][34][35] ]. However, in case of small chemicals, it appears that the molecules can become entrapped in the yolk that represents a dense amphiphilic environment consisting largely of cholesterol (40% of total lipid), phosphatidylcholine (17%), and phospholipo-glycoproteins (i.e., vitellogenins) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, PC and IP microinjections represent excellent alternatives. We further demonstrated that the IY exposure route should be avoided and hence care needs to be taken when analyzing results from this type of exposure, even though it has been widely implemented and automated [ 17,22,34 ]. Finally, we also provide a mathematical model to predict the relative uptake of compounds as a function of time which can offer an invaluable input for future translational research and safety assessment applications.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the chosen approach are the requirements for manual microinjection and the positioning of embryos in agarose cavities under a stereomicroscope, which can lead to a significant workload in screening scenarios. Microinjection could be potentially automated using recently demonstrated robotic injection systems, thus further increasing throughput and reducing variability [37,38]. Manual orientation of embryos takes about 15–20 min per 96-well plate; however, it is still an order of magnitude faster than traditional mounting techniques such as embedding in low melting agarose.…”
Section: Discussionmentioning
confidence: 99%
“…The image-processing algorithm is based on neural networks, which were successfully applied in zebrafish research. 6,7 It can be subdivided into two procedures: first, a preprocessing procedure identifies the position of the object (zebrafish embryo), and cropping is performed. Second, a deep learning algorithm that was trained on 1000 annotated images is used for image classification to distinguish between fertilized embryos in 2-to 16-cell stage and unfertilized zebrafish eggs or artifacts.…”
Section: Fig 1 (A-c)mentioning
confidence: 99%